Pengaruh Campuran Ampas Sagu Dan Ampas Tahu Fermentasi Dengan Kapang Monascus purpureus Dalam Ransum Terhadap Kualitas Telur Puyuh - Suslina A. Latif (Jurnal Embrio, 2011)
This experiment was conducted for combination of sagos waste and tohu waste fermented by Monascus purpureus (SWTF) in ration to determined the egg quality of Quail. It’s used a complete randomize design (CRD) with 4 treatments and 5 replications. The treatments were arranged as follows: 1) basic ration (0% SWTF in ration); 2) 5% SWTF in ration; 3) 15% SWTF in ration, and 4) 15% SWTF in ration. The rations were formulated iso protein 20% and iso energy 2800 kkal/kg ration. The parameters of this study were colesterol of egg yellow, lipid of egg yellow and the colour of egg yellow. The results of this study showed that colesterol of egg yellow, lipid of egg yellow and the colour of egg yellow were significantly affected (P<0,05) by all treatment. Combination of sagos waste and tohu waste fermented by Monascus purpureus can used until 15% in the Quail, which was able to decrease collesterol (128,67 mg/dL) and lipid (7,22 %) of yellow egg and increase of the color of yellow egg (8,80 %)